The impact of ferritin on the disassociation of HbA1c and mean plasma glucose. Issue 6 (14th December 2020) - Li, Yufeng; Zhang, Fang; Zhang, Xiuying; Fu, Zuodi; Wang, Lianying; Zhao, Cuiling; Guo, Guangxia; Zhou, Xianghai; Ji, Linong
Abstract: Objective: To explore the impact of ferritin level on the disassociation of glycated hemoglobin A1c (HbA1c) and mean plasma glucose (MPG). Reseach Design and Methods: We used a 2012‐2013 cross‐sectional survey conducted in Pinggu district, Beijing including 3095 Chinese participants aged 25‐75 years. We categorized their glycemic status by interviewing for diagnosed diabetes and by measuring HbA1c, fasting plasma glucose (FPG), and 2‐hours post‐load plasma glucose (2‐hours PPG). We fitted a multivariable regression model to explore the impact of ferritin on the association of HbA1c or glycated albumin (GA) and mean plasma glucose. Results: A total of 5.65% of participants were diagnosed as diabetes using HbA1c criteria, and 9.79% using oral glucose tolerance test criteria. Compared with males, females had significantly lower hemoglobin levels (159.82 ± 11.56 vs 135.93 ± 12.62) and lower ferritin levels (113.00 [68.55, 185.50] vs 33.40 [12.40, 70.13]). Linear regression analysis performed in different groups classified by different diagnose criterion indicated that the correlation between MPG and HbA1c differs in different tertiles of ferritin (lowest vs middle vs highest: R 2 = 0.507 vs 0.645 vs 0.687 in female; R 2 = 0.415 vs 0.715 vs 0.615 in male), and the association between MPG and HbA1c diminished in the lowest tertile of ferritin. Conclusions: Ferritin level might affect the association between glucose and HbA1c, which should be taken into account when using HbA1c as a diagnosis criterion for diabetes and prediabetes. Abstract : Highlights The current study demonstrated that ferritin level could affect the relationship between HbA1c and mean plasma glucose. Prevalence rate of diabetes based on HbA1c is lower than that of glucose‐based diabetes, which is true across all ferritin levels. 摘要: 目的: 探讨铁蛋白水平如何影响糖化血红蛋白(HbA1c)与平均血糖的关系 研究设计与方法: 我们使用了2012‐2013年在北京市平谷区进行的横断面调查; 这项调查纳入了3095名年龄在25‐75岁的中国受试者。根据了解既往确诊糖尿病史和测量HbA1c、空腹血糖与负荷后两小时血糖对受试者的血糖状况进行分类。通过拟合的多变量回顾模型; 分析铁蛋白水平如何影响平均血糖与HbA1c、糖化白蛋白的关系。 结果: 根据HbA1c标准; 共有5.65%的受试者被诊断为糖尿病; 而根据口服糖耐量试验标准则有9.79%被诊断为糖尿病。相比于男性; 女性受试者的血红蛋白水平显著更低(159.82±11.56 vs. 135.93±12.62 g/L); 铁蛋白水平也更低(113.00 [68.55, 185.50] vs. 33.40 μg/L [12.40, 70.13])。在根据不同诊断标准划分的不同组别中进行的线性回归显示; 平均血糖值和HbA1c之间的相关性在铁蛋白值三分位组中有所不同(最低、中间与最高:女性R 2 = 0.507 vs 0.645 vs 0.687； 男性R 2 = 0.415 vs 0.715 vs 0.615)。平均血糖值和HbA1c之间的相关性在铁蛋白最低三分位组中最低。 结论: 铁蛋白水平可能会影响血糖与HbA1c之间的相关性; 在将HbA1c用作糖尿病和糖尿病前期的诊断标准时应予以考虑。